Forest Management and Biodiversity Conservation - Dinca, Lucian; Zhiyanski, Miglena (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In the current context of global change and global interconnectedness, our role in connecting the dots and finding solutions to current and future problems is very important. When talking specifically about the management of forests, we can see its continuous evolution and, more importantly, its adaptation to contemporary challenges. As is well known, forest ecosystems play an essential role in our economy, human wellbeing and global wellbeing. More specifically, one of the main challenges in forest management is represented by the sustainability of resources and need to conserve biological diversity. The best way is to think globally, to find patterns that repeat themselves and to investigate solutions that can help us to prepare a better future. In this regard, we think that it is essential to review papers that present interesting findings that could guide us. The first step was to select 18 articles from a wide range of countries located on three continents, including Brazil, Bulgaria, Ecuador, Germany, Malaysia, Peru, Poland, Romania, Slovakia, and Slovenia. Our main goal was to analyse the regionally specific aspects, as well as general aspects that can be applied worldwide. Using this approach, we narrowed our research to eight sub-domains: natural and human disturbances, genetics, site conditions, tropical forest, peri-urban forest, forest soils, forest reserves, and mountain ecosystems. These articles tackle themes such as peri-urban forests and their impact on urban agglomerations, ecoturism, cultural heritages and practices from local communities, human interventions and best practices.